Edukasi Bacaan dan Gerakan Sholat dalam Meningkatkan Pemahaman Ibadah Anak - Aliyah, A’imatul; Ananda Surya Lasmita, Dea; Dwi Septiani, Fanisa; Rahayu, Neni; Alawiyah, Syarifah (LP3M IAIFA Kediri, 2024)
Prayer is one of the five important pillars of Islam. This is an obligation that must be fulfilled by humans as a form of worship to Allah. Prayer is not only a religious ritual, but also a way to achieve the goal of perfect worship, by fulfilling the conditions, harmony, and sunnah, and avoiding anything that could cancel it. Even though prayer is not an obligation for young children such as those who have not reached puberty, parents have the responsibility to introduce prayer and other forms of worship from an early age. This research aims to explore the effectiveness of an educational program that focuses on teaching reading and prayer movements for children at TPQ AL – Faqih Gadungan, Puncu, Kediri. The method used in this research is PAR (Participatory Action Research). The research results showed a significant increase in children's prayer abilities because they felt happy and interested in praying both at TPQ and at home. This program also encourages them to get used to praying with full humility and tu'maninah, and to be able to recite the prayer readings fluently and correctly.